Visual Scanning Training, Limb Activation Treatment, and Prism Adaptation for Rehabilitating Left Neglect: Who is the Winner? - Priftis, Konstantinos; Passarini, Laura; Pilosio, Cristina; Meneghello, Francesca; Pitteri, Marco (Frontiers in Human Neuroscience, 2013)
We compared, for the first time, the overall and differential effects of three of the most widely used left neglect (LN) treatments: Visual Scanning Training (VST), Limb Activation Treatment (LAT), and Prism Adaptation (PA). Thirty-three LN patients were assigned in quasi-random order to the three groups (VST, LAT, or PA). Each patient received only one type of treatment. LN patients’ performance on everyday life tasks was assessed four times (over a period of six weeks): A1 and A2 (i.e., the two pre-treatment assessments); A3 and A4 (i.e., the two post-treatment assessments). LN patients in each of the three treatment conditions were treated for the same number of sessions (i.e., 20). The results showed that improvements were present in the majority of the tests assessing the peripersonal space in everyday life activities. Our findings were independent of unspecific factors and lasted for at least two weeks following the end of the treatments. There were no interactions, however, between LN treatments and assessments. We suggest that all three treatments can be considered as valid rehabilitation interventions for LN and could be employed for ameliorating LN signs.